DYNAMICS OF ANTIBIOTIC RESISTANCE OF NOSOCOMIAL PATHOGENS AND STATE OF ANTIBIOTiC THERAPY IN MULTIFIELD CLINIC - S. A. Vereshchagina; M. V. Fedoseeva; G. F. Radnaev; T. S. Belokhvostikova; T. V. Fadeeva (Acta Biomedica Scientifica)
We carried out comparative analysis of the results of microbiological researches and antibiotic resistance of main pathogens of nosocomial infections from 2005 to 2010 years. During this period quota of MRSE (65—74 %), MRSA (22,7—35 %) is stably high and. especially quota of producers of different β-lactamases among other Enterobacteriaceae pathogens (3,2—65 %) increased that caused, significant expenses for antibiotic therapy by carbapenems (22,7—40 %), glycopeptides (2,7—10 %). Monitoring of tendencies of resistance of the most important pathogens of hospital infections optimication of antimicrobial therapy and introduction, of the system of preventive measures allowed, to decrease economic expenses for antimicrobial means to 17,5 %.